The pedagogical competence of teachers in enhancing student creativity based on information technology - Andre , Lesis; Nurhidayah, Josanti; Gafur, Syahrul; Husna, Atina; Meri, Rita; Daniah; Putra, Edo; Zoningsih, Meta Yupitri; Arifin, Muhammad; Tunnazia, Aqilla; Sukinah, Endang; Fauzi, Muhammad; Putra, Debi Kumala (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to understand how teachers' teaching skills can help students improve their creativity by utilizing information technology at one elementary school. The method applied was qualitative, with a case study approach that emphasized teachers in the classroom as the primary focus. Data were collected through interviews, observations, and documentation, then analyzed using qualitative descriptive methods. This research indicates that teachers with practical teaching skills can utilize various digital applications and media in the classroom to encourage students' creativity. Students' creativity increases, as seen by their ability to express ideas, create digital works, and complete school assignments differently. These findings prove that using information technology in learning by pedagogically skilled teachers positively influences the development of students' creativity. This research recommends that teachers improve their pedagogical skills, especially in technological literacy, to improve the quality of the learning process and students' creativity.